Analisis Akuntabilitas Berbasis Sharia Enterprise Theory untuk Upaya Pengembangan Bisnis Rumah Jahit Akhwat di Makassar) - Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aimed to determine the business management system implemented by the Rumah Jahit Akhwat (RJA) including the implementation and role of accountability based on Sharia Enterprise Theory (SET). This study used a qualitative method with a phenomenological approach. The subjects of this research are the owner, employees, and customers of RJA through direct observations, interviews, and documentation. The results of this study indicate that RJA manages its business based on Islamic values ​​such as the application of employee SOPs which are full of Islamic values, contracts in muamalah, and ethics in doing business. SET-based accountability can also be seen in the RJA business such as giving donations to dakwah institutions, conducting social assistance for the poor, and gifts to orphans. This research was conducted at RJA Antang in May 2020.